2005
DOI: 10.1002/ptr.1606
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoid ofDrynaria fortunei protects against acute renal failure

Abstract: The flavonoid fraction (FF) from Drynaria fortunei was investigated to determine its biological activity expression in three acute renal failure animal models. Guinea pigs received 100 mg/kg of gentamicin (GM group), 100 mg/kg of GM plus 10 mg/kg of FF (GMFF group), 10 mg/kg of FF (FF group) or saline (saline group) intramuscularly for 14 days. The blood urea nitrogen (BUN) and creatinine levels were found to be significantly higher in the GM group (22.70+/-3.84 mg/dL, 0.68+/-0.05 mg/dL) than in the GMFF group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…Some of the polyphenols isolated from plants exhibit anticaries activity either due to growth inhibition against mutans streptococci or due to the inhibition of glucosyltransferases (3,13). D. fortunei contains several flavonoids of which biological activities are reported as antinephrotoxicity, kidney primary epithelial tubular cell regeneration, and inhibition of gentamicin ototoxicity and bone resorption (6,9,10). Previously, researchers reported that several essential oils from plants had antibacterial activity against oral bacteria (1).…”
Section: Discussionmentioning
confidence: 99%
“…Some of the polyphenols isolated from plants exhibit anticaries activity either due to growth inhibition against mutans streptococci or due to the inhibition of glucosyltransferases (3,13). D. fortunei contains several flavonoids of which biological activities are reported as antinephrotoxicity, kidney primary epithelial tubular cell regeneration, and inhibition of gentamicin ototoxicity and bone resorption (6,9,10). Previously, researchers reported that several essential oils from plants had antibacterial activity against oral bacteria (1).…”
Section: Discussionmentioning
confidence: 99%
“…The CHCl 3 extract contains naringin, hesperidin, caffeic acid, and procyanidin, but flavonoids was detected only in the n-BuOH extract for presence of organic acid (21,22,25,28,43). Some of the polyphenols isolated from plants exhibit anti-carious effects such as growth inhibition and inhibition of glucosyltransferases against mutans streptococci (44)(45)(46).…”
Section: Discussionmentioning
confidence: 99%
“…Drynaria fortunei (D. fortunei; Gol-Se-Bo in Korean and Gu-Sui-Bu in Chinese), a traditional Korean medicine, has been known to be effective in treating inflammation, hyperlipidemia, arteriosclerosis, rheumatism, gynecological diseases, osteoporosis, and bone resorption (21)(22)(23)(24)(25). It is also used for treatment and prevention of orthopedic diseases, and is known to promote bone healing (22,26).…”
Section: Introductionmentioning
confidence: 99%
“…Drynaria fortunei (Kunze) J. Smith. (Long et al, 2005)); 4 are used for inflammation (e.g. Ficus pumila L.) (Junqing et al, 2009).…”
Section: Representative Plants Of LI Ethnomedicinementioning
confidence: 99%